Protection of vineyards from Zonda wind: Evaluation of forest windbreaks. Mendoza, Argentina - Rodolfo Abel Dematte; Ernesto Gandolfo Raso; Josefina Huespe (Investigaciones Geográficas)
In order to analyze the behavior of the Zonda wind in Mendoza Province, Argentina, the impact of various configurations and levels of optical porosity in forest windbreaks was evaluated. Different configurations of forest curtains were designed, and computational fluid dynamics (CFD) simulations were conducted using OpenFOAM software to assess the protective effect of the windbreaks. The simulations considered the Zonda wind speed type 2 (25 m/s), together with varying levels of optical porosity and geometries of the forest curtains. The results reveal that forest curtains significantly reduce the impact of strong Zonda winds. The effectiveness of these configurations is directly related to the degree of optical porosity (OP) of the forest curtains. A comparison of these findings with the existing literature highlights the importance of OP and the arrangement of forest curtains in mitigating the effects of the Zonda wind. These results corroborate previous studies that have emphasized the crucial role of windbreak structures in protecting agricultural crops from adverse weather conditions. In conclusion, the implementation of forest curtains with a porosity of between 35% and 50% is recommended to achieve effective protection against the Zonda wind in the vineyards of Mendoza. Future research is suggested to further optimize windbreak configurations and improve crop resistance to extreme weather events.